Design and Marketing of Financial Products - Madan, Dilip; Soubra, Badih (Review of Financial Studies, 1991)
[Marketing costs are introduced into the security design environment outlined in Allen and Gale (1988). It is shown that splitting the firm's cash flow between products enhances their investor appeal and reduces marketing costs. We also explain how the extremal product design in Allen and Gale is thereby avoided and how in simple cases, debt, equity, or warrants can be optimal. Furthermore, we illustrate in general terms how the optimal solution employs portfolios of option-type products, and we give an example of two optimal products that share profits in seven of eight states.]